Creativity knowledge of jewelry design measurement using bloom's taxonomy:psychomotor domain - Chaiwat Lochotinant (2019)
© 2019 IEEE. A significant major research in Gem and Jewelry Industry of Thailand state that one of the weakness of this industry is designers' lacking of creativity. What is the creativities knowledge of jewelry designer and what are their activities or behavior in design process? This research aim to review creativities knowledge of Thai jewelry designer and examine its situation in minor perspective. This paper review the jewelry designer's creative behavior in design process and the measurement using Bloom's Taxonomy: Psychomotor Domain as the development of designers' physical abilities and skills measurement. The ultimate designer's learning outcome is on origination level which present originality, novelty and innovation. The samples were selected from ordinary jewelry designers and a success case. Both group were assigned to design a new jewelry collection and finished within 6 hours. All their activities and behaviour were directly observed, interpreted and measured their creativity knowledge. The research found that the Bloom's Taxonomy: Psychomotor Domain is an appropriate tool to measure creativity knowledge and creative behavior of jewelry design process. And the experimental study revealed the activities referred to the statement of designers' lack of creativity.